Enhancing Circulation Services Using E-mail for Alerts and Reminders - Kalbhor, Priyanka; Tyagi, A.K. (DESIDOC Journal of Library & Information Technology, 2010)
The success of information service is more likely to be achieved by adjusting the services to meet specific needs of an individual rather than trying to adapt the individual user to match the output of the information system. This paper provides an insight into the e-services implemented by the Information Centre and Library (IC&L) at Defence Institute of Advanced Technology DIAT (DU), Pune, keeping in view the users’ requirements and their valuable suggestions. Paper also discusses the techniques and tools applied in further simplifying the functioning of the circulation module and ensuring smooth communication between the staff and the users in an otherwise automated library system. http://dx.doi.org/10.14429/djlit.29.258